The Influence of Job Stress on Employee Performance with Employee Engagement as a Mediating Variable at the Baitul Tanwil Muhammadiyah Islamic Savings and Loans and Financing Cooperative (KSPPS BTM) of West Sumatra - Rangga Wahyulis; Chichi Andriani (Greenation International Journal of Tourism and Management, 2026)
This study focuses on explaining and examining the influence of job stress on employee performance, with employee engagement serving as a mediating variable at KSPPS BTM West Sumatra. In this research, the primary emphasis particularly regarding theoretical framework and data analysis is placed on evaluating employee performance as the dependent variable (Variable Y) to better understand how psychological dynamics in the workplace affect the effectiveness of achieved work outcomes. This study focuses specifically on permanent employees within the operational units across KSPPS BTM West Sumatra to capture the direct impact of operational workloads on performance. This quantitative study analyzes data using Structural Equation Modeling (SEM) via SmartPLS. The results of the data analysis demonstrate that job stress exerts a statistically significant negative impact on job performance achievement, while Employee Engagement actively functions as a vital mediating variable that bridges this relationship.